Tolerant and Intolerant Messages: Phenomenology Study of Ulama in West Jakarta - Riswandi; Hadian Rizani; Afdal Mukkaraga (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
Messages that are communicated textually and erroneously are then received by individuals whose lack of religious knowledge encourages tolerant and intolerant behavior, resulting in interfaith violence as happened in Indonesia in the 90s. The research focused on the experience and meaning of the cleric in West Jakarta regarding tolerance and intolerance. The method to conduct this research is qualitative method with a phenomenological approach, through in-depth interviews with ten participants, then analyzed through horizonalization to form a general meaning and in-depth description of tolerance and intolerance.The results show that religious tolerance is interpreted as the freedom of every person to practice worship in accordance with their beliefs on the basis of mutual respect with other people of different religions to create an atmosphere conducive to the common good. This freedom is limited to the scope of each religion which manifests through mutual assistance in helping social and cultural issues.Religious intolerance is characterized by an attitude of disrespect for the worship activities of adherents of other religions arising from understanding textual teachings of religion, blind fanatics, and injustice that inhibits national and state unity. Religious intolerance is perceived not to happen if every religious adherent is willing and able to carry out their respective religious teachings. Forms of intolerance through disagreement and conflicting, destructive, hateful and envious in dealing with religious differences. This research has implications for the expansion of the implementation of the concepts of tolerance and intolerance, and policy changes in multi-religious countries.